2016
DOI: 10.1161/strokeaha.116.013392
|View full text |Cite
|
Sign up to set email alerts
|

Pial Collateral Reactivity During Hypertension and Aging

Abstract: Background and Purpose We investigated vasoactive properties of leptomeningeal arterioles (LMAs) under normotensive conditions and during hypertension and aging that are known to have poor collateral flow and little salvageable tissue. Methods LMAs, identified as distal anastomotic arterioles connecting middle and anterior cerebral arteries, were studied isolated and pressurized from young (18 weeks) or aged (48 weeks) normotensive Wistar Kyoto (WKY18, n=14; WKY48, n=6) and spontaneously hypertensive (SHR18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…We are not aware of previous studies of P t O 2 in SHRs during MCAo. This probably reflects this strain’s poor leptomeningeal collaterals and impaired cerebrovascular autoregulation, resulting from increased vessel stiffness, thicker wall and reduced lumen [ 39 , 41 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of previous studies of P t O 2 in SHRs during MCAo. This probably reflects this strain’s poor leptomeningeal collaterals and impaired cerebrovascular autoregulation, resulting from increased vessel stiffness, thicker wall and reduced lumen [ 39 , 41 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we assessed not only brain tracer retention at the standard 2-3hrs post-administration time, but also FMISO kinetic rate constants, specifically the irreversible trapping constant thought to reflect tissue hypoxia, by dynamically acquiring FMISO brain data since administration time and applying our previously reported quantitative kinetic model [ 32 ]. In addition, to assess the effects of hyperoxia on FMISO uptake in distinct tissue situations, we used both Wistar rats and their spontaneously hypertensive counterparts (SHRs), whose tissue vulnerability to focal cerebral ischemia, namely rate of demise of the severely hypoxic but viable tissue (i.e., the penumbra) [ 33 35 ] and final infarct volume [ 33 , 36 40 ], widely differ as a result of underlying differences in functionality and structure of the pial vascular tree [ 39 , 41 45 ], in turn mimicking clinical heterogeneity. In parallel to testing the effects of hyperoxia on FMISO uptake, and to inform the findings thereof, we also assessed its effects on tissue oxygen tension in both ischemic and non-ischemic cortex in a different group of animals.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that myogenic tone and reactivity are quite different in collateral versus non-collateral arterioles. 174 During hypertension for example, collaterals have increased tone and impaired vasodilation which may result in lower levels of collateral-dependent blood flow, contributing to greater infarct size in response to ischemia. 174 …”
Section: Part I Cerebrovascular Disease: the Prelude To Strokementioning
confidence: 99%
“…high systolic blood pressure, location of the occlusion, presence of extracranial internal carotid artery (ICA) stenosis and poor hydration status are related to worse collateral status. [13][14][15][16][17][18] Further research on potential determinants for poor collateral status could improve our understanding of the collateral system. Possibly, this might help to find ways to improve collateral status during acute ischemic stroke and thus increase chances of a better clinical outcome.…”
Section: Strokementioning
confidence: 99%